Air preheating and exhaust gas recirculation as keys to achieving an enhanced fuel water content range in stratified downdraft gasification. (1st September 2022) - Zachl, A.; Buchmayr, M.; Gruber, J.; Anca-Couce, A.; Scharler, R.; Hochenauer, C.
Graphical abstract: Highlights: Prove of concept that air preheating and EGR enhance valid fuel water content range. Enhanced the allowable fuel water content from 8 to 15 m% to 2–21 m% in given setup. Continuous EGR increased the CGE and reduced the tars in the product gas. Setup-specific ideal operating points with 2–21 m% fuel water content were found. Abstract: The strict fuel water content requirements inhibit the breakthrough of small-scale stratified downdraft gasification CHP plants. The present work was conducted to enlarge the allowable fuel water content range in a wood-chip-driven downdraft gasifier with a nominal fuel load of 90 kW. Specifically, the range was enhanced to include wetter and drier fuel using the methods of air preheating and continuous exhaust gas recirculation (EGR). In this study, three dry (i.e., 8 m%, 5 m%, 2 m%) fuel water content levels were tested with EGR rates ranging from 0 to 62.5 l∙min −1, and three wet fuels (i.e., 8 m%, 17 m%, 21 m%) were tested at three different air temperatures (i.e., 20 °C, 60 °C, 100 °C). Three novel findings were obtained: (1) Air preheating successfully shifted the flame front upward, enlarging the applicable maximum fuel water content from 18 m% to 21 m%, but the gas quality slightly worsened in terms of LHV and tars. (2) The application of EGR lowered the fuel water content limit from 8 m% to 2 m% and even increased the cold gas efficiency and reduced the tar content in the product gas. (3) The evaluations revealed that the flame front must be positioned within a relatively narrow range and close to the reactor throat to ensure steady operation. A safe and long-lasting operating point for each fuel water content was determined. The results of this work indicate that an enhanced fuel flexibility will be possible in stratified downdraft gasifiers in the near future.